MANAJEMEN LOGISTIK HALAL - Fatana Suastrini (Nusantara Hasana Journal, 2023)
Now people's choice has changed from choosing cheap and healthy products to products that are safe, healthy and halal. Because in addition to guaranteed sharia, the product is likely to contain blessings. The management system that regulates the distribution and storage of these products is called the halal logistics system. Problems in halal logistics are caused by low international halal certification, unclear halal guidelines, cooperation and funding, low demand and low standards to measure cost-effectiveness. Based on this description, a study was conducted on halal logistics management. This research is a descriptive research using review method and literature study. The basic concepts of general logistics and halal logistics are actually the same, the difference is that halal logistics is implemented by ensuring the supply chain process separates halal cargo from non-halal cargo. This must be done to avoid cross-contamination and to ensure that during the logistics system the products are halal. When this is done, it will produce halal logistics output that meets the standards desired by the customer. To ensure that the logistics process is always halal, a Halal Assurance System (HAS) is required which is implemented by logistics service providers. One of the emerging technological innovations related to halal logistics is blockchain. the blockchain system will facilitate the separation of the halal industry from halal and haram products and facilitate the implementation of digital transactions and contracts.